Meningkatkan Kemampuan Membaca Kata Menggunakan Media Kartu Bergambar Pada Siswa Tunagrahita Ringan - Ronvy, Al Shaffaat; Hidayat, Hafiz (Jurnal Suloh, 2024)
The research began with problems found in mildly mentally retarded students who had difficulty reading at SLB C Payakumbuh. After examining the characteristics of students, it is easier to read using picture word cards as media. The aim of the research is to prove that picture word card media can improve the word reading ability of mildly mentally retarded students at SLB C Payakumbuh. The type of research used is an experiment in the form of an SSR with an ABA design. Data collection uses techniques in the form of action tests with visual graphic data analysis. There have been 16 meeting sessions divided into 3 conditions. After using picture word card media as a form of intervention, it was proven that this media could improve the word reading ability of students with mild intellectual disabilities.